Extended RKHSM for solving fuzzy differential equations of integer and fractional order / \c Asia Khalaf Salem Albzeirat - Albzeirat, Asia Khalaf Salem (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
This research mainly intends to meet the following objectives ; to extended the RKHSM by involving integer and fractionalderivatives and fuzzy initial conditions ; to develop new algorithms based on the extended RKHSM for solvingFDEFO, FDEFFO, FDESO, FDESFO, FSDEFO, FSDEFFO, FIDEFO and FIDEFFO ; to approximate the solutions of FDEFO, FDEFFO, FDESO, FDESFO, FSDEFO, FSDEFFO, FIDEFO and FIDEFFO using the new algorithms proposed in (ii) ; to analyse the accuracy of the extended RKHSM by comparing the numerical results with the analytical solutions obtained in the integer case.